2015
DOI: 10.1177/1073858415581986
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Deep Brain Stimulation

Abstract: Deep brain stimulation (DBS), applying high-frequency electrical stimulation to deep brain structures, has now provided an effective therapeutic option for treatment of various neurological and psychiatric disorders. DBS targeting the internal segment of the globus pallidus, subthalamic nucleus, and thalamus is used to treat symptoms of movement disorders, such as Parkinson’s disease, dystonia, and tremor. However, the mechanism underlying the beneficial effects of DBS remains poorly understood and is still un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
158
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(163 citation statements)
references
References 98 publications
3
158
1
1
Order By: Relevance
“…Multiple clinical trials have shown that high frequency DBS therapy can be superior to best medical therapy for motor complications in PD (810, 29). Despite clear efficacy of DBS in PD, its mechanism is not well understood and different hypotheses have been proposed (30, 31). Although, discussion of these hypotheses is beyond the scope of this article, it is suggested that DBS, through its excitatory and inhibitory effects on the targeted nucleus, disrupts abnormal information within cortico-basal ganglia-thalamic neural circuits, which results in improvement of motor symptoms (30, 31).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple clinical trials have shown that high frequency DBS therapy can be superior to best medical therapy for motor complications in PD (810, 29). Despite clear efficacy of DBS in PD, its mechanism is not well understood and different hypotheses have been proposed (30, 31). Although, discussion of these hypotheses is beyond the scope of this article, it is suggested that DBS, through its excitatory and inhibitory effects on the targeted nucleus, disrupts abnormal information within cortico-basal ganglia-thalamic neural circuits, which results in improvement of motor symptoms (30, 31).…”
Section: Resultsmentioning
confidence: 99%
“…While lesioning procedures (eg, pallidotomy or thalamotomy) are carried out using radiofrequency ablation or gamma knife radiosurgery, DBS (eg, pallidal or thalamic DBS) uses high-frequency electrical stimulation of the targeted nuclei. Although the therapeutic mechanisms of action are not completely understood, ablative surgeries are believed to destroy abnormally hyperactive circuits in deep brain nuclei, while DBS suppresses abnormally excessive activity in the motor circuitry without significant destruction of the brain tissue 68,69. Neurostimulation, therefore, has largely replaced neuroablation to treat refractory dyskinesias because it is less invasive, adjustable for maximal symptomatic benefit, and reversible in case of adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Electric currents of certain pulsing protocols make it possible to increase, suppress, or distort neuronal activity in the circuits near a particular electrode. 5 This approach has been successfully used to alleviate the symptoms associated with medication-refractory action or resting tremor in patients with essential tremor (ET) or Parkinson’s disease. 14,44,46 The main strength of DBS is that it provides stimulation throughout the lifetime of the implanted device, which generally results in lasting treatments.…”
mentioning
confidence: 99%